Carbon Black Nanoparticles Selectively Alter Follicle-Stimulating Hormone Expression in vitro and in vivo in Female Mice - Avet, Charlotte; Paul, Emmanuel N.; Garrel, Ghislaine; Grange-Messent, Valérie; L’Hôte, David; Denoyelle, Chantal; Corre, Raphaël; Dupret, Jean-Marie; Lanone, Sophie; Boczkowski, Jorge; Simon, Violaine; Cohen-Tannoudji, Joëlle (Frontiers in Neuroscience, 2021)
Toxic effects of nanoparticles on female reproductive health have been documented but the underlying mechanisms still need to be clarified. Here, we investigated the effect of carbon black nanoparticles (CB NPs) on the pituitary gonadotropins, luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which are key regulators of gonadal gametogenesis and steroidogenesis. To that purpose, we subjected adult female mice to a weekly non-surgical intratracheal administration of CB NPs at an occupationally relevant dose over 4 weeks. We also analyzed the effects of CB NPs in vitro, using both primary cultures of pituitary cells and the LβT2 gonadotrope cell line. We report here that exposure to CB NPs does not disrupt estrous cyclicity but increases both circulating FSH levels and pituitary FSH β-subunit gene (Fshb) expression in female mice without altering circulating LH levels. Similarly, treatment of anterior pituitary or gonadotrope LβT2 cells with increasing concentrations of CB NPs dose-dependently up-regulates FSH but not LH gene expression or release. Moreover, CB NPs enhance the stimulatory effect of GnRH on Fshb expression in LβT2 cells without interfering with LH regulation. We provide evidence that CB NPs are internalized by LβT2 cells and rapidly activate the cAMP/PKA pathway. We further show that pharmacological inhibition of PKA significantly attenuates the stimulatory effect of CB NPs on Fshb expression. Altogether, our study demonstrates that exposure to CB NPs alters FSH but not LH expression and may thus lead to gonadotropin imbalance.